Observation on Powder-Post Beetle, Dinoderus minutes (Fab.) (Coleoptera: Bostrichidae) Infesting Dry Bamboo and Wooden Materials in Bangladesh - Ahmed, KN; Zulfiqr, CM (Journal of Bio-Science, 2007)
J. bio-sci. 14: 131-132, 2006